Loadbearing capacity of infill masonry walls considering the deformation‐based membrane effect - Schmitt, Michael (Mauerwerk, 2018)
According to currently valid codes, it is not possible to determine the loadbearing capacity of unreinforced infill walls considering the deformation‐based membrane effect by incorporating the exact support conditions. One reason for this is the lack of a validated calculation procedure, which in addition to the equilibrium conditions also realistically represents the compatibility conditions of these systems. In the present paper, therefore, a new non‐linear analytical calculation procedure is presented. The main focus of the analysis of walls subject to area loading is the incorporation of the support conditions and thus the consideration of the deformation‐based membrane compressive force. Through generalised formulation and a standardised notation of the determination equations, different material behaviours and various support conditions can be taken into account with few parameters. On the action side, both lighter loading like wind loads and heavier loading like explosion loads can be considered. Through the implementation of the partial factor concept, it is possible to comply with the requirements of European codes and thus ensure the applicability of the analysis model. Nach den derzeit gültigen Normen ist es nicht möglich, die Tragfähigkeit von unbewehrten ausfachenden Mauerwerkswänden unter Berücksichtigung der verformungsbasierten Membranwirkung durch Einbeziehung der exakten Lagerungsbedingungen zu ermitteln. Ein Grund dafür ist ein fehlendes validiertes Berechnungsverfahren, welches neben den Gleichgewichts‐ auch die Verträglichkeitsbedingungen dieser Systeme realistisch abbildet. In dem vorliegenden Beitrag wird daher ein neues nichtlineares analytisches Berechnungsverfahren zur realistischen Ermittlung der Tragfähigkeit von ausfachenden Mauerwerkswänden vorgestellt. Hauptaugenmerk wird in der Bemessung der flächenbelasteten Wände auf die Einbeziehung der Lagerungsbedingungen und damit auf die Berücksichtigung der verformungsbasierten Membrandruckkraft gelegt. Durch allgemeine Formulierungen und eine normierte Schreibweise der Bestimmungsgleichungen können unterschiedliche Werkstoffverhalten und verschiedene Lagerungsbedingungen mit wenigen Parametern berücksichtigt werden. Auf der Einwirkungsseite können sowohl geringe Belastungen wie Windlasten als auch höhere Beanspruchungen wie Explosionslasten berücksichtigt werden. Durch die Implementierung des Teilsicherheitskonzeptes ist es möglich, die europäischen Normenanforderungen zu erfüllen und dadurch die Anwendbarkeit des Bemessungsmodells sicherzustellen.